1990
DOI: 10.1007/bf00403321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein kinase C modulators on the leucocyte Na+/H+ antiport in Type 1 (insulin-dependent) diabetic subjects with albuminuria

Abstract: It is uncertain why only one third of Type 1 (insulin-dependent) diabetic patients develop nephropathy. One suggestion is the inheritance of a predisposition to essential hypertension. We have previously found elevated Na+/H+ antiport activity and a raised intracellular pH in leucocytes from hypertensive and Type 1 diabetic subjects with albuminuria using a novel double ionophore fluorimetric technique. These changes are not found in Type 1 diabetic subjects without albuminuria. We wished to test the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

1991
1991
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
0
17
1
Order By: Relevance
“…The maximal relaxation by acetylcholine (E^,, expressed as percentage of the level of norepinephrine-precontracted tension) and the acetylcholine concentration that produced a half-maximal relaxation (pD 2 …”
Section: Discussionmentioning
confidence: 99%
“…The maximal relaxation by acetylcholine (E^,, expressed as percentage of the level of norepinephrine-precontracted tension) and the acetylcholine concentration that produced a half-maximal relaxation (pD 2 …”
Section: Discussionmentioning
confidence: 99%
“…Of interest, many of the physical and functional abnormalities demonstrated in cell membranes from hypertensive patients, including Na+/H+ antiport activation, can be reproduced by the activation of PKC ( 11). With regard to diabetes mellitus, more recent studies have shown that the PKC inhibitor staurosporine can restore to normal the previously elevated leucocyte Na+/H+ antiport activity ofdiabetic patients, thereby suggesting that diabetes-induced increases in Na+/H+ antiport activity may be dependent on PKC activation (19). Diabetes mellitus is characterized by the development of hyperglycemia, and we have recently shown that elevated extracellular glucose concentrations (20 mM) induce a sustained activation of PKC in cultured VSMC (20,21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these observations, Donnadieu and co-workers (4,5) found no evidence of Na+/ examine this issue further, we have employed a sensitive assay to detect Na+/Ca2+ exchange activity in human lymphocytes, i.e., cytosolic Na+-dependent Ca2" influx. Identifying Na+/Ca2" exchange activity in lymphocytes would increase our understanding of functional alterations in cation transport in several pathological conditions. White blood cells from subjects exhibiting essential hypertension (6)(7)(8)(9) and diabetes mellitus (10,11) have been studied to gain insight into cellular Na+ and Ca2" transport abnormalities. However, in order for lymphocytes to serve as a model for cellular Na+ and Ca2" homeostasis, they should express the cation transport mechanisms found in the target cells known to be affected in these disorders.…”
Section: Introductionmentioning
confidence: 99%